L’injure dans la société libanaise Les mots, le sens - Aïda Kanafani-Zahar (Revue des Mondes Musulmans et de la Méditerranée)
In the Lebanese society, the social organisation, the practises of sociability and hospitality, the sense of honor, lie on the same culture, the arabic culture, christians and muslims have towards insults the same sensibility. They draw from the same semantic corpus, but two kinds of insults can nontheless be distinguised: the double insult, while taking for target the sexual honor of women, the lineage, or the religion, aims to reach the person as well as its group, and the simple insult that touches the person only, whether by means of malediction or the use of negative attributes. Remains the problem of the relationships between the words and the meaning, whether words are diverted from their meaning when the context is inappropriate, or whether the meaning goes beyond the words and resists to different strategies of avoidance.